Norry's disease in a child: clinical case - T. A. Kryuchkova; E. V. Matvienko (Лечащий Врач)
Recently, there has been a tendency to increase the incidence of hereditary diseases in children around the world. Norrie's disease is a rare genetic disease that is characterized by an abnormality in the development of the retina and congenital blindness. The article presents a clinical case of Norrie's disease in a child aged 4 years and 2 months. From the anamnesis of life it is known that the patient is from 1 pathologically proceeding pregnancy and childbirth. During pregnancy, the mother of the child had gestosis, a threat of abortion, a high titer of antibodies to Chlamydia trachomatis. At the age of 1 month, an ophthalmologist was first diagnosed with: Norrie's disease? Repeatedly examined at the Research Institute of Eye Diseases named Helmholtz (Moscow). Surgical treatment of retinal detachment is considered futile. For the first time, the diagnosis of Norrie's disease was confirmed by the molecular genetic method at the age of the patient 9 months. At the age of 11 months, the child was hospitalized in the Children's Clinical Hospital (St. Petersburg), where he underwent 1 stage of surgery on his left eye – lensvitrshvartectomy, subretinal fluid drainage, and iris plastic surgery. After 2 months, surgical treatment was performed on the right eye – lensvitrshvartectomy, drainage of the subretinal fluid, plastic iris. The postoperative period was uneventful, but the prognosis of specialists regarding vision is unpromising. After a year, the child underwent repeated organ-sparing surgeries in the right eye. Positive dynamics was noted, consisting in a decrease in the degree of pathological displacement anteriorly of the equatorial sections of the retinal tissue. The article notes the main stages of the diagnosis of Norrie's disease in a patient, presents the features of the clinical course of the disease and monitoring the sick child in dynamics. The disease of the organs of vision was probably formed as a result of complex antenatal pathology during the first half of pregnancy in the mother of the child.